KAJIAN PSIKOLINGUISTIK PEMEROLEHAN BAHASA PERTAMA DALAM RANAH FONOLOGI DAN MORFOSINTAKSIS - Elsa Mulya Karlina (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2026)
A phenomenon evident in early childhood first language acquisition is the gradual emergence of language skills: children initially produce simple sounds, then develop into more structured utterances. This study aims to describe first language acquisition in the areas of phonology and morphosyntax. The research method uses a qualitative-descriptive approach with a psycholinguistic framework, through analysis of data from observations, recordings, and recordings of children's speech in source studies. The results indicate that at the phonological level, children are able to produce dominant vowels such as [a], [i], [e] and initial consonants such as [b], [p], [m], [n], and [t], accompanied by simple syllable patterns of CV, CVC, and CVCV. In terms of morphosyntax, children begin to produce meaningful utterances, ranging from single words to combining several words into simple sentences, although structural simplifications and inaccuracies in meaning still occur in some utterances. These findings emphasize the role of family and environmental interactions as primary drivers of first language development.